Estudo da assembleia de quirópteros (Mammalia: Chiroptera) da Gruta do Riacho Subterrâneo – município de Itu – SP - Rocha, Alana Drielle (Universidade Federal de São Carlos, 2015)
The objective of the present study was to analyze the taxonomic composition and structure of a bat assemblage of Gruta do Riacho Subterrâneo, a granitic cave located the municipality of Itu, São Paulo State, Brazil, and to verify the influence of abiotic variables on its structure. The main hypotheses were: a) The cave studied is important to the regional diversity of bats functioning as a shelter to some important bat species. b) There are changes in the composition and abundance of the bat assemblages as a consequence of abiotics changes observed in the studied area. Five samplings were carried out along the twelve months.The captures were performed using mist nets and bats were measured and ringed. The catch effort, relative abundances, the species acumulation curve and the influence of abiotic variables on chiropterofauna were determined. The influence of abiotics variables were analysed by multiple regression and canonic correspondence analysis, performed in the R program. A total of 113 individuals were captured in the cave and its surrounding area, from which more than 80% belonged to the family Phyllostomidae and the remaining to the Vespertilionidae. The acumulation curve for the samples indicated that the assymptotic portion of the curve was not reached. The most abundant species were Carollia perspicillata (30,8%), Desmodus rotundus (29.%) and Myotis sp. (23.4%) whereas some other species as Anoura geoffroyi, Micronycteris sp., Chiroderma doriae, Sturnira tildae and Eptesicus diminutus had single events of capture. There was no significant relationship between the abiotic variables measured and the community structure along the time, indicating that probably other factors might be influencing the population dynamics. The cave community has high species richness encompassing five important trophic guilds, particularly the frugivorous one, revealing the importance of the Gruta do Riacho Subterrâneo cave for the conservation opf local diversity. Based on the functional aspects of thisconservation and also restauration of the cave surrounding area will be essential to diversity conservation for this important group of mammals.
Keywords: Morcego; Cavernas; Sazonalidade; Influência; Qualidade ambiental; Cave bats; Biodiversity; Trophic guilds; Reproduction patterns; São Paulo; CIENCIAS BIOLOGICAS::ECOLOGIA